Satisfying urban Africa's taste for milk - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Demand for milk and dairy products is growing fast in Africa. Simultaneously, dairy imports are becoming less available andmore expensive. This provides an opportunity for increasing local production and processing capacity, both of which can...